Mechanical and Acoustic Emission Responses of Rock Fragmentation under Disc Cutter Penetration - Qi Liu; Yucong Pan; Penghai Deng (Advances in Civil Engineering)
To better understand the rock fragmentation mechanism and optimize cutter design and selection for rock excavation by TBM, a set of three-dimensional indentation tests was conducted with different rock and cutter types. Acoustic emission (AE) monitoring technique was employed to capture the information of the rock damage evolution real-timely. It is found that the penetration by using the constant cross section (CCS) cutter tends to induce inconspicuous rock chips formation before the sudden occurrence of the macrocrack, but that by using the V-type cutter tends to induce gradual rock fragmentation accompanied by the multiple local rock chips formation and the sawtooth force-penetration curve. Meanwhile, rock fragmentation models for CCS and V-type cutters were compared, and the spatio-temporal evolution of AE events was quantitatively analyzed to reflect the rock damage zone development process. Results indicate that the V-type cutter has greater penetration ability and the CCS cutter can cause larger unit damage zone radius. Microscopic observation by using the scanning electron microscope (SEM) reveals that the fracture mechanism for the crushed zone of rock is mainly shear type and that for the major crack is tensile type. It does not matter with rock types or cutter types.